1975
DOI: 10.1113/jphysiol.1975.sp011164
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive osmometer function of juxtaglomerular cells in vitro.

Abstract: 4. The juxtaglomerular cells were four to five times more sensitive to changes in osmolarity through sucrose than sodium chloride concentration. Changes in potassium chloride concentration (7-57 mM) had little effect.5. Sodium chloride had no direct ionic effect on renin release outside its osmotic properties.6. The findings support a previous proposal that the rate of renin release in vitro relates directly to the volume of the juxtaglomerular cell. The hypothesis is developed that a similar mechanism may und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 15 publications
2
28
0
Order By: Relevance
“…6). Although surprising at first view, the observed stimulation of renin secretion by high [K+]o is in accordance with the findings of Beierwaltes et al (1981) and Frederiksen et al (1975), obtained with similar preparations of rat JG cells. It should be noted in this context that high extracellular potassium also stimulates renin secretion in the isolated perfused rat kidney (Fray 1980) and hog kidney slices if extracellular calcium is low, and inhibits it at normal or.…”
Section: Resultssupporting
confidence: 91%
“…6). Although surprising at first view, the observed stimulation of renin secretion by high [K+]o is in accordance with the findings of Beierwaltes et al (1981) and Frederiksen et al (1975), obtained with similar preparations of rat JG cells. It should be noted in this context that high extracellular potassium also stimulates renin secretion in the isolated perfused rat kidney (Fray 1980) and hog kidney slices if extracellular calcium is low, and inhibits it at normal or.…”
Section: Resultssupporting
confidence: 91%
“…The lack of change in renin release in response to the addition of 0-5 % DMSO is in accordance with the prediction that volume changes should be minimal or absent due to the high permeability of cell membranes to DMSO. The reduced or abolished response in renin release (first challenge) to lowering superfusate osmolality by reducing the sucrose 152 L. BA UMBACH COLOHICINE AND CYTOCHALASIN IN RENIN RELEASE 153 concentration or the sodium chloride concentration is hardly an effect of the increased initial osmolality since previous studies on isolated glomeruli have shown that the response to a hypotonic challenge was independent of the initial total osmolality in the range 285-355 m-osmole/kg (Frederiksen et al 1975). A decreased permeability to renin is also unlikely, since DMSO caused no change in basal renin release.…”
Section: Discussionmentioning
confidence: 99%
“…Based on earlier observations (Frederiksen et al 1975;Baumbach, Leyssac & Skinner, 1976) it has been proposed that the renin release process under study is somehow coupled to the JG-cell volume and its active regulation. The effects of colchicine and the vinca alkaloids on renin release are difficult to interpret in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, changes in renin secretion occurs only with a short delay after osmolarity changes. It has been demonstrated that the nature of osmotically active particles is important for their effect on renin secretion, the effect on exocytosis is directly related to the reflection coefficient of the particle (Frederiksen et al 1975). From this observation juxtaglomerular cells are assumed to behave as sensitive osmometers.…”
Section: Osmotic Forcesmentioning
confidence: 99%